Clitic Doubling: A New Syntactic Category in Hittite - Sideltsev, Andrej V. (Altorientalische Forschungen, 2011)
The present paper seeks to differentiate between appositive dislocation and clitic doubling. Appositive dislocation is constituted by a stressed or unstressed pronoun plus a full NP in one clause. The pronoun and the full NP are coreferential, but lexically the full NP is not identical to the antecedent of the pronoun, nor does the full NP possess any discourse function, merely introducing additional information about the referent. Clitic doubling is constituted by an enclitic pronoun plus a full NP and has two varieties. In the first the full NP is not only coreferential with but also lexically identical to the full NP of the preceding clause, thus coding discourse status change of the NP. Clitic doubling of the second type is not only lexically different from the full NP of the preceding context, neither is it coreferential with it. The discourse function in this case is to mark the new topic.